Simple analysis of daylight saving time effects in Belgrade climate and latitude - Grujić Marija (Spatium, 2018)
Contemporary controversy about daylight saving time (DST) is mainly derived from different standpoints in studies investigating the positive and negative effects of the clock shift during summer period. From the standpoint of energy savings, most studies have consensus that the summertime clock shift in middle latitudes, with a large difference between winter and summer daylight hours, contributes to energy savings in buildings. Belgrade’s mid-latitude, moderate-continental climate has a six-month long heating season and a three-month cooling season. The annual domination of the heating period assumes that the demand for heating energy also dominates in the annual energy breakdown for average office buildings. Since DST covers mainly summer time, the energy breakdown in office buildings during the DST period is dominated by the energy demand for lighting and cooling. The shift of time ahead of standard time during the DST period causes a shift in temperature, daylight availability and solar energy resources and thus a shift in the potential for the utilisation of the surrounding energy. This paper investigates how the application of DST in Belgrade’s climate and latitude influences the change of climate parameters relevant for the cooling and lighting energy demand in office buildings.